Rancangan Jaringan Fiber to The Tower (FTTT): Studi Kasus di PT. Trans Indonesia Supercorridor menggunakan Metode Link Power Budget Berbasis Web (Journal Digital Technology Trend, 2023)
The Fiber to The Tower (FTTT) network calculation website using the power link budget method at PT. Trans Indonesia Supercoridor provides a robust solution for companies to streamline their field network data calculation processes. This platform offers comprehensive features including network feasibility assessment, centralized storage of calculation data, detailed result presentation, and efficient management of network calculation records. Internal testing yielded a promising usability rating of 90%, affirming its practicality. External evaluation by PT. Trans Indonesia Supercoridor users showed an 80% acceptance rate, underscoring its suitability for corporate deployment. The website enhances operational efficiency by simplifying complex network calculations, thereby supporting informed decision-making and facilitating smoother network management practices. Its reliable performance in both internal and external assessments position it as a valuable tool in optimizing telecommunications infrastructure planning and implementation.